Management and administration skills for the mental health professional - O'Donohue, William T.; Fisher, Jane E. (Jane Ellen), 1957- (Practical resources for the mental health professional., 1999)
Psychologists receive several years of specialized study on the brain, behavior, and mental health, but despite the fact that over half ultimately end up in administrative or managerial roles, they receive no formalized training in the skills necessary to be successful in these roles. This book is the first of its kind to target the managerial and administrative skills necessary for the mental health professional. The book discusses practical information such as how to deal with personnel issues, how to set budgets and allocate resources, and how to document progress and maintain schedules in.